A new variety of Panax (Araliaceae) from Lam Vien Plateau, Vietnam and its molecular evidence - Duy, Nong Van; Trieu, Le Ngoc; Chinh, Nguyen Duy; Tran, van Tien (Phytotaxa, 2016)
A new variety of Panax, P. vietnamensis var. langbianensis is described from Lang Bian Mountain, Lam Vien Plateau in southern Vietnam. It is visually distinct from other two varieties of P. vietnamensis (var. vietnamensis, var. fuscidiscus) by having the shorter petiolules 8–11 mm long, leaflet apex acuminate, pedicels 0.4–0.6 cm, petals smaller, disk prominent, and styles typically 2 (or rarely 1). The recognition of the new variety is supported by the evidence of molecular sequence data from three markers (ITS1-5.8S-ITS2, 18S rRNA and partial matK) in addition to morphological consideration. The new variety is known only from one population from the locality where the type specimens were collected. The species occurs in an area of only approximately 1 km2 with a population size of approximately 100–200 individuals. Therefore it should be regarded as critically endangered (CBB2acb (ii,iii,v); C2a(i); E) according to the IUCN Red List Categories and criteria.